Digital telephony - Bellamy, John (Wiley series in telecommunications, 1991)
"The book stresses how systems operate and the rationale behind their design, rather than presenting rigorous analytical formulations . [It provides] the practicality and breadth essential to mastering the concepts of modern communications systems." -Telecommunication Journal In this expanded new edition of his bestselling book, telephony expert John Bellamy continues to provide telecommunications engineers with practical, comprehensive coverage of all aspects of digital telephone systems, while addressing the rapid changes the field has seen in recent years. Bellamy discusses the near-complete conversion to digital technology in telephone networks worldwide, examines both existing and emerging technologies, and explores the intricacies of carrying voice over data networks as well as the use of telephone networks for carrying data for Internet access. He emphasizes system design, implementation, and application, but also correlates the practice to communications theory.